Electrophoretic mobility of cervico-vaginal fluid protein of crossbred cows - JAIN, AKLANK; DAVE, B K (The Indian Journal of Animal Sciences, 2014)
Crossbred cows (18) were assigned to 3 groups of 6 cows each, viz,normal (T1), repeat breeding (T2) and true anoestrus cows in which oestrus was induced by injecting pregnant mare serum gonodotropin (T3). The total protein concentration in the cervico-vaginal fluid was higherin the normally cycling (T1) and induced estrus cows (T3) being 131.05 and 125.11 mg/100 ml, respectively, whereas, it was only 81.93 mg/100 ml in repeat breeder (T2) crossbred cows. Electrophoretic analysis of the cervico-vaginal fluid indicate nonsignificant differences in the number of protein bands, mobility of protein and protein percentage. The conception rate in these artificially inseminated cows were also not significantly different.